Crime in Scotland 1660-1960 - Kilday, Anne-Marie, author.
1 online resource (348 pages)
Keywords: Scotland has often been regarded throughout history as "the violent north", but how true is this statement? Does Scotland deserve to be defined thus, and upon what foundations is this definition based? This book examines the history of crime in Scotland, questioning the labelling of Scotland as home to a violent culture and examining changes in violent behaviour over time, the role of religion on violence, how gender impacted on violence and how the level of Scottish violence fares when compared to incidents of violence throughout the rest of the UK. This book offers a ground-breaking contribution to the historiography of Scottish crime. Not only does the piece illuminate for the first time, the nature and incidence of Scottish criminality over the course of some three hundred years, but it also employs a more integrated analysis of gender than has hitherto been evident. This book sheds light on whether the stereotypical label given to Scotland as 'the violent north' is appropriate or in any way accurate, and it further contributes to our understanding of not only Scottish society, but of the history of crime and punishment in the British Isles and beyond.